Pengaruh Relationship Marketing Investment Dan Nilai-Nilai Bersama pada Niat untuk Menyumbang Melalui Kepercayaan Calon Donatur - Tanti Handriana (Forum Manajemen Indonesia (FMI), 2014)
This study tested the effect of relationship marketing investment and shared values to trust, and also tested the effect of trust on intentions of prospective donors to donation. Thus, this study examines the role of trust in relationship marketing in nonprofit organizations. Data was collected using questionnaires from 124 respondents in the form of prospective donor in badan/lembaga amil zakat. Analytical techniques used to examine the relationships between research constructs in the form of shared values, relationship marketing investment, trust and intentions to donate was the technique of Structural Equation Modeling (SEM). The results showed that the shared values affecting trust of the prospective donor in badan/lembaga amil zakat. This study also proves that the trust has a positive effect on intention prospective donors to donation. Keywords: shared values, relationship marketing investment, trust.